The Impact of Green Accounting Implementation On Profitability - Yuliza, Arma; mela, Fefti Yulian (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2024)
The purpose of this study is to determine the effect of implementing green accountin to profitability company mining in Indonesia 2019 period – 2021. Data secondary used in the research was obtained from report annual company mining in stock Exchange Indonesia year 2019 – 2021. Method Which used is method quantitative with population size is 43 company. Saturated sampling method is used in this study. So that the data obtained as much as 129 for three years starting from 2019-2021.